Penatausahaan Aset Tanah Daerah Hasil Pemekaran Kabupaten Jayapura - Raharjo, Taufik; Wirawan, Aditya; Shintasari, Reni; Samodra, Fery (Journal of Political Issues, 2024)
Abstract The aim of this research is to study the implementation of administration of regional assets in the form of land by the Jayapura City Government after the expansion of Jayapura Regency. Apart from that, this research tries to uncover obstacles in the implementation of administering regional assets in the form of land and identifies solutions that can be implemented to reduce obstacles that arise after regional expansion. This research uses a descriptive qualitative approach with data sources originating from the results of in-depth interviews with credible informants according to the objectives of this research. The results of this research show that the administration of regional assets or regional property/ Barang Milik Daerah (BMD) has been implemented well due to collaboration with related parties. However, there is a note that several assets with high value are still owned by the Jayapura Regency Government, whereas assets which are movable assets were not handed over so that movable assets require new procurement.